Prolonged high-pressure treatments in mammalian skeletal muscle result in loss of functional sodium channels and altered calcium channel kinetics. - Friedrich, Oliver; Kress, Kai; Hartmann, Martin; Frey, Benjamin; Sommer, Karl; Ludwig, Horst; Fink, Rainer (Cell Biochemistry and Biophysics, 2006)
Activation and inactivation of ion channels involve volume changes from conformational rearrangements of channel proteins. These volume changes are highly susceptible to changes in ambient pressure. Depending on the pressure level, channel function may be irreversibly altered by pressure. The corresponding structural changes persist through the post-decompression phase. High-pressure applications are a useful tool to evaluate the pressure dependence as well as pressure limits for reversibility of such alterations. Mammalian cells are only able to tolerate much lower pressures than microorganisms. Although some limits for pressure tolerance in mammalian cells have been evaluated, the mechanisms of pressure-induced alteration of membrane physiology, in particular of channel function, are unknown. To address this question, we recorded fast inward sodium (I(Na)) and slowly activating L-type calcium (I(Ca)) currents in single mammalian muscle fibers in the post-decompression phase after a prolonged 3-h, high-pressure treatment of up to 20 MPa. I(Na) and I(Ca) peak amplitudes were markedly reduced after pressure treatment at 20 MPa. This was not from a general breakdown of membrane integrity as judged from in situ high-pressure fluorescence microscopy. Membrane integrity was preserved even for pressures as high as 35 MPa at least for pressure applications of shorter durations. Therefore, the underlying mechanisms for the observed amplitude reductions have to be determined from the activation (time-to-peak [TTP]) and inactivation (tau(dec)) kinetics of I(Na) and I(Ca). No major changes in I(Na) kinetics, but marked increases, both in TTP and tau(dec) for I(Ca), were detected after 20 MPa. The apparent molecular volume changes (activation volumes) deltaV(double dagger) for the pressure-dependent irreversible alteration of channel gating approached zero for Na+ channels. For Ca2+ channels, deltaV(double dagger) was very large, with approx 2.5-fold greater values for channel activation than inactivation (approx 210 A3). We conclude, that in skeletal muscle, high pressure differentially and irreversibly affects the gating properties and the density of functional Na+ and Ca2+ channels. Based on these results, a model of high pressure-induced alterations to the channel conformation is proposed.